TEACHER AWARENESS, IDENTIFICATION OF LEARNING DIFFICULTIES, AND EFFECTIVE TEACHING STRATEGIES FOR ENGLISH GRAMMAR MASTERY - Maryam Sorohiti; Harun Noor Rochman Nugraha; Fitria Rahmawati (Indonesian EFL Journal, 2024)
English grammar learning poses a significant challenge for teachers, particularly in countries characterized by linguistic and cultural diversity, such as Indonesia. Although English language learning, which inherently encompasses grammar, is compulsory in Indonesian junior high schools, students face difficulties due to the absence of engaging learning strategies. This descriptive qualitative research delved into the perspective and experiences of three Grade 10 teachers from two private high schools in Yogyakarta. The focus was on their awareness of students' difficulties in learning grammar, their perception of the challenges encountered by students in mastering grammar, and their effective teaching strategies aimed at assisting students in overcoming these challenges. The research was conducted through one-on-one, in-depth interviews with the participating teachers. This study revealed that teachers possess the awareness to identify their students' difficulties in learning grammar. In addition, the challenges faced by students primarily stem from their limited exposure to English and lack of motivation. To address these challenges, teachers employ effective strategies such as guided spoken sentence construction and the use of games. These strategies not only provide a structured approach to grammar learning but also make the process engaging and enjoyable for students. By acknowledging the unique needs of their students and utilizing effective teaching methods, teachers play a crucial role in facilitating the mastery of grammar skills.Keywords: EFL Teachers, Grammar, Awareness, Obstacles, Teaching Methods